Synthesis of novel 8-formyl-7-hydroxy-4-methylcoumarin derivatives - Hülya Çelik Onar; Didem Erdoğan (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
This study was initiated by7-hydroxy-4-methylcoumarin 1synthesis according to the Peckmann reaction with resorcinol andethylacetoacetate. This compound wasconverted into 8-formyl-7-hydroxy -4-methylcoumarin 2 compound by the Duffreaction. This aldehyde obtained wasreacted with 6-amino-1,4-benzodioxane and 2-amino benzamide, which have theirspecific biological activities, to synthesize the original two novel compounds.While 3 (7-Hydroxy-4-methyl-8-[(2,3-dihidro-1,4-benzodioxin-6-yl)iminomethyl]-2H-1-benzopiran-2-on)is obtained as a coumarin schiff base, ring closure was observed at 4 (2-(2’-Hydoxy-5-methylcoumarin-1-yl)-2,3-dihidro quinazoline-4(1H)-on). Ourcompounds are thought to exhibit biological activity. Their structures wereidentified by IR, 1H NMR, 13CNMR , MS analysis.